An ignition delay time and chemical kinetic study of ethane sensitized by nitrogen dioxide. (1st November 2017) - Deng, Fuquan; Pan, Youshun; Sun, Wuchuan; Yang, Feiyu; Zhang, Yingjia; Huang, Zuohua
Abstract: Nitrogen dioxide (NO2 ) is a dominant component of NOx pollution in combustion of internal combustion engines and gas turbines. Its sensitization on ignition of ethane which is a main component of natural gas has been investigated in this experimental and kinetic study. Ignition delay times of NO2 /C2 H6 /O2 /Ar mixtures, with blending ratios of NO2 :C2 H6 of 0.3:1 and 1:1, were measured in a shock tube. Experimental conditions cover a range of pressures (1.2–20 atm), temperatures (950–1700 K) and equivalence ratios (0.5–2.0). Similarly to our previous work of CH4 /NO2 (Deng et al., 2016) [14], NO2 addition promotes the reactivity of ethane and reduces the global activation energy particularly at higher pressures ( p > 5.0 atm) and lower temperatures ( T < 1175 K), whereas it only presents a limited effect at low pressure (1.0 atm) and higher temperatures ( T > 1175 K). Furthermore, an opposite effect of NO2 addition is observed in both the experiments and the simulations at different temperature regimes. Compared to fuel-rich mixture, NO2 addition exhibits more significantly promoting effect on the ignition of fuel-lean mixture under given NO2 concentration. Four literature kinetic mechanisms and an updated mechanism proposed in this study have been compared to simulate the new ignition delay time data and the literature data. Overall, the proposed model is capable of reproducing the experimental results measured by various facilities over a wide range of conditions. The proposed model is thus used to carry out the sensitivity and flux analyses to clarify the chemistry interaction between NO2 and ethane. Based on the kinetic analyses, the impact of NO2 has been expounded at different conditions.